The Advances in Civil Engineering Materials Selected Papers of the ICACE 2018 held in Batu Ferringhi, Penang Malaysia on 9th -10th May 2018 - Awang, Mokhtar; Isa, Mohamed Hasnain (Lecture Notes in Civil Engineering,, 2019)
This volume presents a compilation of research works in civil engineering. All manuscripts in this volume were presented during the 2nd International Conference on Architecture and Civil Engineering (ICACE 2018) which was held at Parkroyal Hotel, Penang, Malaysia on 09-10 May 2018. The editor(s) of the proceeding would like to express the utmost gratitude and thanks to all reviewers in the technical team for making this volume a success.